TANTANGAN DAN STRATEGI LITERASI INFORMASI PERPUSTAKAAN DI ERA DIGITAL - Arta, Mohammad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This research discusses the challenges and strategies of library information literacy in the digital era, focusing on the development of electronic collection publishing in Indonesia. In the digital era, access to information has undergone significant changes with the emergence of electronic collections such as e-books, electronic journals, and multimedia. However, there are challenges that need to be overcome, such as limited access, cybercrime actions, copyright issues, and budgetary constraints. By adapting to technological developments and fostering collaboration between institutions, digital libraries have the potential to expand access to library collections and strengthen literacy culture in society. The research method used is qualitative with a literature review, with analysis using open coding techniques. The main themes identified include reading interest trends and literacy culture, publishing transformation in the digital era, and analysis of literacy culture in electronic collection publishing. By understanding the challenges and implementing appropriate strategies, it is expected that library information literacy will increase in supporting the development of electronic collection publishing in Indonesia.